If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x(x + 3y) = 18 (x * -2x + 3y * -2x) = 18 Reorder the terms: (-6xy + -2x2) = 18 (-6xy + -2x2) = 18 Solving -6xy + -2x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + -6xy + -2x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + -6xy + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '-2'. -2(9 + 3xy + x2) = 0 Ignore the factor -2.Subproblem 1
Set the factor '(9 + 3xy + x2)' equal to zero and attempt to solve: Simplifying 9 + 3xy + x2 = 0 Solving 9 + 3xy + x2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4x*2-9=0 | | 4xy+2x+6y+3=0 | | (y-5)-(y+7)=8y | | X-26=4 | | 4q=92 | | 3t-3=9+9t | | 5c+12=7c+11.84 | | 10x+x^2=84 | | -3x-30x-75=0 | | -10y^2-4(5y^2-8)+6y= | | -x^2-4x=-47 | | -5+8(x-3)=17x+2-9x | | -x^2-4x= | | 18=0.2x+5 | | -3(-7-6n)=-11+2(4+5n) | | 52+14m=318 | | -9+10=m-9 | | 10x-4=6x+2 | | 7x+10=-60-7x | | 7x+10=-60-7x | | 2m+14-5(m-1)=9m-(5m-4)-8m+9 | | (6+x)*(10+x)=144 | | m^2-14+49=0 | | 33n-195=234 | | mx^2+(2m+3)x+(m-1)=0 | | -9m+51-9(m-3)=3m-(4m-4)-2m+1 | | 7x+17=52 | | 8+2n=20 | | 7+3n=19 | | 2y-6=5x+8 | | 9(r+8)= | | 24=x-36 |